The Reading of Russian Literature in China - Gamsa, M. author. aut Link
VII, 227 p.
Keywords: This book traces the profound influence that Russian literature, which was tied inseparably to the political victory of the Russian revolution, had on China during a period that saw the collapse of imperial rule and the rise of the Communist Party.